Using social–ecological syndromes to understand impacts of international seafood trade on small-scale fisheries. (November 2015) - Crona, B.I.; Van Holt, T.; Petersson, M.; Daw, T.M.; Buchary, E.
Highlights: We evaluate multidimensional local outcomes of seafood market integration as social–ecological syndromes. Results show that market integration, without accompanying institutional strategies, often lead to unsustainable fisheries. Explanatory factors derive from different scales suggesting a need for multi-level institutional frameworks. Globalized seafood trade is creating similar vulnerabilities locally around the world—confirming the notion of tele-connectivity across geographic space. Abstract: Globalization has increased the speed and flow of people, information, and commodities across space, integrating markets and increasing interdependence of geographically dispersed places worldwide. Places historically driven by largely local forces and market demands are now increasingly affected by drivers at multiple scales. Trade is particularly important in driving these changes and more fish is now exported to international markets than ever before. When small-scale fisheries are integrated into global markets, local social–ecological systems change with potentially both positive and negative impacts on livelihoods, economics and ecology, but few studies systematically investigate how and why the outcomes of market integration vary from case to case. This paper systematically assesses multiple (social, ecological, economic and institutional) local effects of market integration in cases around the world by drawing on the global environmental change syndromes approach. Furthermore, we examine the factors contributing to the syndromes observed. Our analysis identifies three distinct social–ecological syndromes associated with international seafood trade. Results suggest that the presence of strong and well-enforced institutions is the principal factor behind the syndrome characterized by sustained fish stocks, while a combination of weak institutions, patron–client relationships, high demand from China and highly vulnerable target species explain the other two syndromes distinguished by declining stocks, conflict and debt among fishers. A key finding is that the factors emerging as important for explaining the different syndromes derive from different scales (e.g. local market structures vs distant market characteristics), indicating a need for multi-level governance approaches to deal with the effects of market integration. Furthermore, the meta-analysis shows that each syndrome encompasses fisheries from multiple continents. This suggests that the increasingly global nature of the seafood trade appears to be driving local dynamics by creating similar conditions for vulnerabilities in localities around the world, lending support to the notion of tele-connectivity across geographic space.